Redesigning for Collaborative Learning Environment: Study on Students' Perception and Interaction in Web 2.0 Tools. (20th February 2015) - Leow, Fui-Theng; Neo, Mai
Abstract: In this study, Gagne's instructional events were incorporated into Jonassen's model for designing constructivist learning environment (CLE) to enable collaborative learning, which mediated by web 2.0 tools. By factor analysing the survey response from 182 students in previous study, 'peer interaction' component was identified, and therefore used as the coding category for the content analysis, to study students' comments and posts in web 2.0 tools. It was found that peer interaction can be further elaborated into different aspects, such as forming cross-checking and expressing personal thoughts. The next study will focus on other identified components in collaborative learning environment.